Short Communication: Sequence variation of DREB2 gene as a potential molecular marker for identifying resistant plants toward drought stress - DWI SETYO RINI (Smujo International, 2019)
Abstract. Rini DS. 2019. Short Communication: Sequence variation of DREB2 gene as a potential molecular marker for identifying resistant plants toward drought stress. Nusantara Bioscience 11: 35-43. Drought stress is the most destructive environmental factor affecting agricultural productions worldwide. Drought stress affects around 60 million hectares of agricultural land in Indonesia. Therefore, the selection of crops that can grow well and survive under drought is necessary to overcome the problem of decreased crop yield during stress conditions. DREB2 (Dehydration Responsive Element Binding2) belongs to the Transcription Factor (TF) gene families as a master regulator of plant responses under stress. Due to increased expression by stress, this gene can be used as a molecular marker to identify resistant plants toward drought. However, study the sequence variation of DREB2 is required to understand the character of this gene related to its function at a molecular level. The sequence of DREB2 in several plants was obtained from NCBI and aligned to determine the similarity of the regions. Even though variations were found in N-terminal of DREB2 sequences studied, there was a high similarity of the sequences in the DNA binding domain. It has been predicted that this domain is part of a conserved region in the sequence of DREB2 gene. This domain is then proposed to be used for primer designing purposes to study DREB2 gene expression between plant species.  Keywords: DREB2, drought stress, sequence variation